2022
DOI: 10.1186/s12876-022-02203-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1-3p targets CENPF to repress tumor-relevant functions of gastric cancer cells

Abstract: Here we noted significantly downregulated miR-1-3p in gastric cancer (GC) tissue compared with adjacent normal tissue through qRT-PCR. Lowly expressed miR-1-3p correlated GC progression. Overexpressing miR-1-3p could restrain tumor-relevant cell behaviors in GC, while miR-1-3p inhibitor treatment triggered the opposite results. Moreover, dual-luciferase reporter gene detection identified specific binding sites of miR-1-3p in CENPF 3’untranslated region. Upregulating miR-1-3p constrained cell progression of GC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Tan et al found that C1GALT1 could promote migratory ability and proliferation of BLCA YTS-1 cells in vitro and in vivo, whereas its carcinogenicity was suppressed by miR-1-3p through binding directly to its 3′-untranslated region (3′-UTR) [23]. Zhou et al reported that miR-1-3p negatively mediated CENPF to hamper gastric cancer progression [24]. Du et al suggested that inhibited colorectal cancer cell proliferation and metastasis through suppressing YWHAZ mediated epithelial-mesenchymal transition (EMT) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al found that C1GALT1 could promote migratory ability and proliferation of BLCA YTS-1 cells in vitro and in vivo, whereas its carcinogenicity was suppressed by miR-1-3p through binding directly to its 3′-untranslated region (3′-UTR) [23]. Zhou et al reported that miR-1-3p negatively mediated CENPF to hamper gastric cancer progression [24]. Du et al suggested that inhibited colorectal cancer cell proliferation and metastasis through suppressing YWHAZ mediated epithelial-mesenchymal transition (EMT) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that miR-1-3p was low expressed in gastric cancer tissues and cells, and was closely related to the size of the tumor. Overexpression of miR-1-3p inhibits the proliferation and invasion of gastric cancer cells by targeting stanniocalcin 2 (STC2) or centromere protein F (CENPF), in which CENPF is also associated with migration [ 56 , 57 ]. Interestingly, miR-1-3p can target glucose-6-phosphate dehydrogenase (G6PD) to affect the Warburg effect (aerobic glycolysis) of gastric cancer cells.…”
Section: Role Of Mir-1-3p In Tumor Occurrence and Developmentmentioning
confidence: 99%